Ultrastructural Features of Neurovascular Units in a Rat Model of Chronic Compressive Spinal Cord Injury - Xu, Jinghui; Long, Houqing; Chen, Wenli; Cheng, Xing; Yu, Haoyang; Huang, Yangliang; Wang, Xiaobo; Li, Fobao (Frontiers in Neuroanatomy, 2018)
Chronic spinal cord compression is the most common cause of spinal cord impairment worldwide. Objective of this study is to assess the ultrastructural features of the neurovascular unit (NVU) in a rat model of chronic compressive spinal cord injury, 24 SD rats were divided into two groups: the control group (n = 12), and the compression group (n = 12). A C6 semi-laminectomy was performed in the control group, whereas a water-absorbent polyurethane polymer was implanted into the C6 epidural space in the compression group. The Basso Beattie Bresnahan (BBB) scores and the somatosensory evoked potentials (SEP) were used to evaluate neurological functions. Transmission Electron Microscopy (TEM) was performed to investigate the change of NVU at the 28th day after modeling. Compared with the control group, the compression group shows a significant reduction (P < 0.05) of BBB score and a significant severity (P < 0.05) of abnormal SEP. TEM results of the compression group showed a striking increase in endothelial caveolae and vacuoles; a number of small spaces in tight junctions; a significant increase in pericyte processing area and vessel coverage; an expansion of the basement membrane region; swollen astrocyte endfeet and mitochondria; and the degeneration of neurons and axons. Our study revealed that damage to NVU components occurred followed by chronic compressive spinal cord injury. Several compensatory changes characterized by thicker endothelium, expansive BM, increased pericyte processing area and vessel coverage were also observed.